الخلايا الجذعية كتدخل مبكر لتحسين لغة أطفال متلازمة داون - السلاموني، سهام أحمد (رابطة التربويين العرب, 2015)
تهدف الدراسة الحالية إلى تقديم تصور واضح حول الخلايا الجزعية كتدخل مبكر لتحسين اللغة لدى أطفال متلازمة داون، ولتحقيق ذلك فقد عملت الباحثة على مراجعة بعض الأدبيات والدراسات الحديثة التي تناولت هذا الموضوع من زوايا متعددة. وقد ركزت الدراسة على تحديد ما هية الخلايا الجذعية وكيفية الحصول علهيا واستخدامها كعلاج مناسب، وتقديم معلومات عن أطفال متلازمة داون والمشكلات التي تواجههم وأثرها في التوافق النفسي والمجتمعي، وتحديد إستراتيجية التدخل المبكر لتحسين اللغة لأطفال متلازمة داون باستخدام الخلايا الجذعية. وقد توصلت هذه الدراسة إلى أن تأخر النمو اللغوي ناتج عن الحالة الصحية ونضج الأجهزة والأعضاء الحسية المرتبطة بعملية الكلام، بالإضافة إلى الذكاء وميول الطفل الذاتية، وكذلك يستجيب الطفل لمستوى أقل من الإثارة الناتجة عن انخفاض مستوى التوتر العضلي في الوجه واللسان وعدم تطور الدماغ وعدم التآزر البصري الحركي، بالإضافة إلى ضخامة اللسان وتأخر نمو الأسنان مما يؤثر على إصدار الأصوات, وأفادت نتائج تحليل الدراسات السابقة بأن استخدام برامج التدخل المبكر واشراك الوالدين فيها يساعد بصورة واضحة في تحسن المشكلات اللغوية لدى أطفال متلازمة داون، الأمر الذي يؤكد أهمية التدخل المبكر لعلاج مثل تلك المشكلات. وقد أكدت النتائج أيضاً على إمكانية علاج المشكلات المختلفة لأطفال متلازمة داون بما فيها المشكلات اللغوية، وذلك باستخدام الخلايا الجذعية. ولحل مشكلة تشوه الخلية الجذعية لطفل متلازمة داون أمكن التوصل إلى طريقة تمنع عمل الكروموسوم الثالث بالخلية لتصبح خلية طبيعية يمكن أن تنقسم إلى خلايا تحاكي النسيج الذي تزرع به. وتأمل الباحثة استخدام الخلايا الجذعية كتدخل مبكر لتحسين اللغة وتطويرها لدى أطفال متلازمة داون، والذي يمكن تعميمه على جميع المشكلات التي يعاني منها هؤلاء الأطفال سواء كانت لغوية أو حركية أو سمعية، وهذا ما اتضح من الدراسات المعملية والتي يمكن أن تجرى مستقبلاً على الأطفال أنفسهم.
The present study aims to provide a clear vision about stem cells early intervention to improve the language among children with Down's syndrome, To achieve this, the, researcher has worked on the review of the literature and some recent studies that dealt with this subject from multiple angles. The study focused on identifying what deity stem cells and how to get it and use it as a remedy appropriate, and provide information on children with Down’s syndrome and the problems they face and their impact on psychological adjustment and societal, and define a strategy of early intervention to improve language for children with Down’s syndrome using stem cells. The findings of this study suggest that delayed language development resulting from the state of health and maturity of the organs and sensory organs associated with the process of speech, as well as intelligence and tendencies of the child self as well as respond to the child for a lower level of excitement generated by the low level of muscle tension in the face and tongue and lack of brain development and the lack of synergy visual motor, in addition to the magnitude of the tongue and teeth growth retardation, which affects the issuance of the votes. And reported the results of an analysis of previous studies that the use of early intervention programs and the involvement of parents which helps clearly in the improvement of the problems of language among children with Down’s syndrome, which underlines the importance of early intervention to treat such problems. The results also confirmed the possibility of the treatment of different problems for children with Down syndrome, including the problems of language, using stem cells. To solve the problem of deformation of a stem cell to a child with Down syndrome was reached on the way to stop the work of the third chromosome cell to become a normal cell can be divided into cells that mimic tissue grown with it. And hopes researcher to use stem cells as an intervention early to improve the language and developed with children with Down syndrome, which can be circulated to all the problems afflicting these children, whether linguistic or motor or audio, and this is what turns out from laboratory studies, which can be. conducted in the future on the children themselves.
Keywords: الخلايا الجذعية -- الأطفال المعوقين -- متلازمة داون -- النمو العقلي -- تعليم الأطفال